High stature and body mass might affect the occurrence of Schmorl’s nodes - Trzciński, Dawid; Myszka, Anna; Piontek, Janusz (Anthropological Review, 2017)
Schmorl’s nodes are vertical herniation of intervertebral discs into the body of neighbouring vertebral endplate. Notwithstanding extensive studies, no consensus has been reached in the subject of their possible etiology. It is hypothesized that physical stress, trauma and high axial loading are the key factors in the occurrence of this pathology. The main objective of the current work is to reevaluate the relationship between stature and body mass and Schmorl’s nodes. For this purpose, skeletal samples from Lithuania (44 males and 19 females) and Poland (97 males and 60 females) were used. The study confirmed that Schmorl’s nodes are age-independent, and more frequent in males (12.63% on the superior and 19.32% on the inferior surface of vertebrae) than in females (6.23% and 12.29% respectively). Obtained results also suggest that high stature (e.g. Spearmann correlation for superior: R=0.20 p=0.017, and inferior: R=0.31 p=0.000 surface of vertebrae) and body mass (R=0.25, p=0.002 and R=0.32, p<0.001, respectively) are factors that increase the risk of Schmorl’s nodes. Authors hypothesize that the afore-mentioned body size traits alter loadings acting on intervertebral discs, and rigidity of the spine.